KEDUDUKAN ANAK LUAR NIKAH PERSPEKTIF HUKUM ISLAM - Maimun Maimun (State of Islamic Institute Langsa, 2017)
Marriage is an attempt to maintain human survival and protect nasab. But sometimes the protection is often tarnished with the existence of an adultery or relationship outside of marriage. Often these relationships result in an illegitimate offspring who is of course a descendant of which adultery results have a position in law different from the position of the legitimate child. Therefore, an outof-wedlock child as a result of an adultery by his or her parents will not be entitled as to the right earned by the child legitimately, especially in the case of inheritance, the outsider will not be able to obtain the inheritance of his biological parents before there is recognition from his biological parents, an outsider is a child born outside a legal marriage according to syara '. The scholars have agreed that one can not be denied to his father. As a legitimate child, if the child is born less than six months after the marriage contract, because according to them the shortest interval that must exist between the birth of the child and the marriage is six months. This means that if a child is born not reaching six months after the parents of the marriage contract, then the child can not be fathered to his father as a legitimate child